A review of aerodynamic aspects of ram wing research - Ashill, P. R. (College of Aeronautics, 1963)
Theoretical and experimental research into the aerodynamics of ram wings is reviewed. The theories of two-dimensional and finite wings in ground effect are discussed and mention is made of the various experimental techniques available for ground effect tests. The possible shortcomings of each method are noted. In the final section it is concluded that there is a considerable need for research into the dynamic stability of ram wings. It is suggested that any dynamic tests should include measurements of the effect of the movement of the ground, as might be experienced when in transit. over a wavy sea.